The Philosophical Power of Civic Education 21st Century in Indonesia - Gunawan Santoso (LPPM of NAROTAMA UNIVERSITY, 2021)
Civic education is a subject and course that has a great responsibility in building the character of democracy and the tolerance of students, because civic education is a moral education and must be administered at every level of education from elementary to college. Civic education is subjects and courses of moral education that should be able to minimize even the conflict among learners. This research uses the method of literature analysis with grounded theory is a qualitative research method that uses a number of systematic procedures to develop a theory compiled inductive. Research grounded theory, this research inductive research techniques, emphasizes observation and develops a base of